Islamic Spirituality and Job Satisfaction on Teachers' Performance at Madrasah Tsanawiyah Negeri in Southeast Sulawesi - Yuana, Indira; Fauzih, Fauzih; Samdin, Samdin; Restiana, Selvia; Roslan, Astil Harli (International Journal of Islamic Thought and Humanities, 2025)
This study analyzes the influence of Islamic spirituality and job satisfaction on teachers' performance. The primary focus is to examine how these two variables shape teacher performance within Islamic-based educational environments. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The sample consisted of 165 teachers from state Islamic junior high schools (Madrasah Tsanawiyah Negeri) across Southeast Sulawesi Province. Data were collected through a structured questionnaire, with validity and reliability tests conducted on the research instruments. The results indicate that Islamic spirituality and job satisfaction positively and significantly affect teacher performance. These findings suggest that spiritual values and job satisfaction play a crucial role in enhancing the quality of teacher performance. The study recommends strengthening spiritual aspects and workplace well-being as part of broader strategies to improve educational quality.